2015
DOI: 10.7439/ijbar.v6i2.1636
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lipid Parameters , Liver Function Test , CRP and MDA (as a marker of lipid peroxidation) in Chronic Cigarette Smokers

Abstract: Background: The addictive liability and pharmacological effects of smoking are primarily mediated by the major tobacco alkaloid nicotine. Cigarette smoke may promote atherogenesis by producing oxygen-derived free radicals that damage lipids. Cigarette smoking is associated with impaired endothelium-dependent vasodilatation and cardiovascular disease (CVD). Aim: The Aim of our study was to determine the Level of lipid profile, liver function, CRP and MDA in cigarette smokers. Method: A Total No. of 100 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…The plasma MDA levels are higher in smokers than in non-smokers. This study was conducted on 100 subjects with 50 healthy subjects and 50 chronic or heavy smokers and obtained significant results with p-value = 0.0001 (p <0.05) [13]. Other studies have also shown increased levels of MDA in rats exposed to cigarette smoke as many as 40 cigarettes per day (p<0.05) [14].…”
Section: Resultsmentioning
confidence: 76%
“…The plasma MDA levels are higher in smokers than in non-smokers. This study was conducted on 100 subjects with 50 healthy subjects and 50 chronic or heavy smokers and obtained significant results with p-value = 0.0001 (p <0.05) [13]. Other studies have also shown increased levels of MDA in rats exposed to cigarette smoke as many as 40 cigarettes per day (p<0.05) [14].…”
Section: Resultsmentioning
confidence: 76%
“…Damage to hepatic cells will increase levels of amino transferase resulting in increased levels of SGOT and SGPT. [5][6] The study by Kumar (2015) also showed that smoking can increase levels of SGOT and SGPT.…”
Section: Discussionmentioning
confidence: 97%
“…Adanya Nitrosative stress dan tingginya Reactive Oxygen Species (ROS) merupakan radikal bebas akibat rokok dapat menyebabkan kerusakan sel dan jaringan, disfungsi mitokondria, inflamasi, serta kelainan neurodegenerative (Bazan, N. G. et al 2012) (Eske, J. dan Sampson, S. 2019). Selain itu stres oksidatif dapat menghasilkan radikal bebas yang menyebabkan terjadinya peningkatan aktivitas proteolitik sehingga kadar plasma protein menjadi rendah dan berefek pada terjadinya kerusakan sel ( Kumar, S.,. et al 2015) .…”
Section: Bahan Dan Metodeunclassified